Visual discourse of statues of symbolic figures Christ as a model (An analytical study): مصطفى ممتاز نوري الياور (Al-Academy, 2021)
The topic of this research deals with an analytical study of the nature of the visual sent by the sculptural monument of the person of Christ around the world, the nature of this monument, the manner of its embodiment, the mechanism of reception for each of the societies that this monument addressed to them, how it was reflected on them, how it was reflected on them, and whether these works are related to their culture or not, I discussed this study All this, and the researcher has established theoretical research axes for the research according to the desired goal of this study, which is the definition of the mechanism of visual discourse of statues of Christ around the world and were as follows: (The first axis: the discourse and visual discourse between the term and the concept), (The second axis: the gestural system and its applications ), (The third axis - Christian arts), while the fourth axis: it dealt with the selection and analysis of samples, which resulted in the following results:1. The visual discourse of the statues of Christ in the contemporary period has shifted from a discourse with a religious significance that introduces the characteristics of religion and God, to an artistic and aesthetic discourse that follows the social and environmental references and what is imposed by the taste and intellectual reference of the recipient.2. The recipient requires shapes that simulate the formal systems that resemble him in order to be more positive in receiving and communicating. As a result, the artist succeeds in delivering his aesthetic visual speech.3. The spatial environmental pressure is very evident in the various statues of Christ, especially in the countries of the same continent in which most of their peoples share somewhat similar formal features.